Revisiting the Role of the Armenians in the Battle of Mantzikert - Vratimos, Antonios (Reti Medievali Rivista, 2020)
It is well known that after Romanos Diogenes’ sound defeat at Mantzikert in 1071 A.D., the Armenians founded their own principalities in Byzantine territory. Yet, their role in the battle has not been examined systematically until now. According to Michael the Great, the patriarch of the Syrian Orthodox Church, the Armenians were the first to desert from the army. Whereas this was accepted as truth in the past, more recently historians have questioned the historicity of his statement. This study proposes to solve the problem, and concludes that the Historia of Attaleiates contains evidence that corroborates the desertion of the Armenian soldiers.